IMMOBILIZATION OF HUMIC ACID ONTO CHITOSAN USING TOSYLATION METHOD WITH 1,4-BUTANEDIOL AS A SPACER ARM - Uripto Trisno Santoso; Radna Nurmasari; Dewi Umaningrum; Sri Juari Santosa; Bambang Rusdiarso; Dwi Siswanta (Indonesian Journal of Chemistry, 2012)
Immobilization of humic acid (HA) onto chitosan using tosylation method with 1,4-butanediol as a spacer arm has been evaluated. Chitosan was phthaloylated selectively using phthalic anhydride in dimethylformamide as solvent with addition of 5% water (v/v) as cosolvent prior to be tosylated. N-phthaloyl-chitosan and HA were tosylated using tosyl chloride in excess and triethylamine as catalyst at temperature < 10 °C for 12 h. The 6-O-tosyl-N-phthaloyl-chitosan was reacted with 1,4-butanediol in order to obtain a spacer arm attached chitosan. The 6-O-butanol-N-phthaloyl-chitosan was activated by reacting with tosyl chloride. For evaluation on immobilization of HA on chitosan with and without spacer arm, 6-O-tosylbutane-N-phthaloyl-chitosan was reacted with HA and the 6-O-tosyl-N-phthaloyl-chitosan was reacted with HA. The HA immobilized onto chitosan was characterized by XRD and FTIR spectrophotometric method. The result showed that HA can be immobilized covalently onto chitosan after attaching 1,4-butanediol as spacer arm onto 6-O-tosyl-N-phthaloyl-chitosan and activating the product with tosyl chloride, but HA cannot be reacted directly onto 6-O-tosyl-N-phthaloyl-chitosan.